Healthcare Delivery and Emergency Preparedness on Svalbard: A Study of Norwegian and Russian Practices and Cooperation - Wæhler, Turid Austin (UiT Norges arktiske universitet, 2024)
The aim of this thesis is to explore Norwegian and Russian approaches to healthcare delivery and emergency preparedness on Svalbard and to examine potential effects from a closer cooperation. The methods were interdisciplinary. A systematic review was performed to assess studies about health on Svalbard (article 1). Thereafter, a literary analysis explored concepts of health and illness in Norwegian and Russian fiction (article 2). Finally, through a semi-structured interview study, Norwegian and Russian stakeholders were questioned about approaches to and potential for cooperation in healthcare and emergency preparedness (article 3). Overall, the findings show no evidence of an increased risk for specific diseases on Svalbard but indicate particular challenges in terms of local fauna and occupational health. Examples include a small possibility of being attacked by polar bears and an increased risk of mining- and snowmobile accidents. The health challenges on Svalbard are otherwise comparable to mainland Norway. Furthermore, the findings show that Norway and Russia experience roughly the same challenges related to healthcare delivery and emergency preparedness, and that there is a certain level of cooperation between the countries in these fields. Factors such as existing relations and communication systems facilitate further cooperation, while different systems for healthcare delivery and emergency preparedness and differences in language and culture are potential obstacles. Expanding cooperation between the countries is considered to entail positive effects. However, the war in Ukraine and consequent EU sanctions against Russia are substantial obstacles to extended cooperation between Norway and Russia on Svalbard. Målet med denne avhandlingen er å utforske norsk og russisk tilnærming til helsetjenester og beredskap på Svalbard, og å undersøke mulige effekter av tettere transnasjonalt samarbeid på disse områdene. For å oppnå dette målet, er tverrfaglige metoder benyttet. En systematisk litteraturgjennomgang ...